The demand for oil products in developing countries - Gately, Dermot, 1943-; Streifel, Shane S. (Washington, D.C. : World Bank, 1997)
This study examines the growth in demand for eight major oil products for 37 developing countries over the 1971-1993 period. It analyzes the relationships and changes over time for income, population, energy and oil product demand for these developing countries. It also shows the extreme heterogeneity among these countries, not only among themselves but compared with the relative homogeneity of the developed countries.
Includes bibliographical references (p. 87-88).
oif 04/11/14
Loan
Keywords: Petroleum industry and trade -- Developing countries